The legal legacy of the Special Court for Serra Leone - Jalloh, Charles (New York, NY, USA : Cambridge University Press, 2020)
"This book examines whether the Special Court for Sierra Leone ("SCSL"), which was established jointly through an unprecedented bilateral treaty between the United Nations ("UN") and Sierra Leone in 2002, has made jurisprudential contributions to the development of the nascent and still unsettled field of international criminal law. The work, which focuses on the main legal legacy of the SCSL, opens with an examination of the historical and political circumstances which led to the outbreak of a notoriously brutal civil war in Sierra Leone which lasted between March 1991 and January 2002 and led to the deaths of approximately 75,000 people. Following a discussion of the creation, jurisdiction and the trials conducted by the SCSL, the author examines the SCSL's unique personal jurisdiction over persons bearing "greatest responsibility" for the serious crimes committed in Sierra Leone and its implications of its use in future ad hoc international tribunals; the prosecution of the novel crime of "forced marriage" as other inhumane acts of crimes against humanity; the prosecution of the war crime of recruitment and use of children under the age of fifteen for the purpose of using them to participate in hostilities; as well as issues of immunity for the serving head of state of Liberia, which President Charles Taylor sought to invoke to block his own trial for international crimes before the SCSL. The book then discusses the status of blanket amnesties under international law, and critically evaluates the SCSL's ruling that such a domestic measure could not block prosecution of universally condemned crimes before an independent international tribunal. Lastly, the book evaluates the tenuous interaction between truth commissions and special courts 2 given both their simultaneous operation in Sierra Leone and distinctive mandates aimed at reconciliation and punishment. The author demonstrates that the SCSL, as the third modern international criminal tribunal supported by the UN, made some useful jurisprudential additions on many of these topics, and in some cases broke new ground, and that these represent a valuable legal and judicial contribution to the development of the nascent field of international criminal law. Charles C. Jalloh is Professor of Law at Florida International University, USA and a member of the UN International Law Commission where he has served as the Chairperson of the Drafting Committee (70th session) and Rapporteur (71st session). Jalloh, who is the Founding Editor of the African Journal of Legal Studies and African Journal of International Criminal Justice, has published widely on issues of international criminal justice. In 2018, he was the Fulbright Distinguished Chair in Public International Law at the Faculty of Law, Lund University and the Raoul Wallenberg Institute of Human Rights and Humanitarian Law in Sweden. His prior work experience includes as a legal adviser in the Department of Justice, the Special Court for Sierra Leone and the International Criminal Tribunal for Rwanda. His related books include, as lead editor, Consolidated Legal Texts for the Special Court for Sierra Leone (Brill, 2007), The Law Reports of the Special Court for Sierra Leone (Brill, AFRC Case, 2012
CDF Case, 2013, Taylor Case, 2015
RUF Case, 2020) and The Sierra Leone Special Court and Its Legacy: The Impact for Africa and International Criminal Law (Cambridge, 2014)"
Based on author's thesis (doctoral - Universiteit van Amsterdam, 2016) issued under title: Judicial contributions of the Sierra Leone tribunal to the development of international criminal law
Includes bibliographical references and index
Keywords: International criminal courts -- Netherlands; International criminal law